Scaling Community-Based Breeding Programs for Sheep and Goats - Berhie, Asmelash; Getachew, Tesfaye; Muluneh, Dagne; Tessema, Kejela; Dagnew, Mulatu; H/Giorgis, Geremew; Alemayehu, Amelmal; Yeshaw, Shanbel; Haile, Aynalem; Belay, Berhanu (Ministry of Agriculture Ethiopia, 2025)
The Community-Based Breeding Program (CBBP) for sheep and goats in Ethiopiahas proven to be a successful genetic improvement project since its establishment in2009. This program effectively involves local communities in various aspects, such asidentifying and collecting data on animals, managing and using breeding sires,utilizing traditional knowledge, and mobilizing community flocks to enhance theirsheep and goat stock. It achieves this by engaging community members inparticipatory selection processes based on the estimated breeding value of the animalswhile also considering the specific needs of the community.